An investigation of learners' perceptions of homework in relation to the learning of mathematics : case studies in the northern townships of Port Elizabeth - Wendt, Gabriele Erika (Rhodes University, Faculty of Education, Department of Education, 2000)
Matriculation pass rates in South Africa, especially in Mathematics, have been poor. The literature and personal experience suggests that a problem with homework may be a factor in this. In order to discover how Port Elizabeth learners from ex-DET schools perceived and experienced Mathematics homework, and the nature of such homework, ten case studies of Grade 11 learners were done. While conducting and analyzing the case studies, a pattern emerged from the findings, which together with some new questions, needed to be explored on a larger sample population. In order to do this and to be able to generalize the findings, four follow-up studies in the form of surveys on Mathematics homework were conducted at nine schools. These studies involved a learner questionnaire, a teacher questionnaire, the timing of learners as they did set Mathematical problems and the analysis of common errors made by the learners while doing the problems. The findings revealed that learners received too little homework too infrequently and did it inefficiently and ineffectively. The learners worked too slowly, did not complete the homework, left out the difficult problems and made numerous unnecessary mistakes. However, most of the learners claimed to have enough time available to do their homework and spent approximately one hour on Mathematics homework when it had been assigned. Many of the misconceptions and the resultant errors originated from work that should have been well covered in previous grades. However, parts of the syllabi were omitted in previous grades and completion of the syllabus and homework was only seriously considered in Grade 12. Some implications of the findings for educational practice and further research are discussed.
Keywords: Homework -- South Africa -- Port Elizabeth; Mathematics -- Study and teaching -- South Africa -- Port Elizabeth; Mathematics -- Study and teaching -- South Africa -- Case studies; Education and state -- South Africa; Education -- South Africa